Predictors for Current Intrauterine Device Use Compared With Female Sterilization Among U.S. Women [210]. (May 2015) - Shakir, Jamilah M.; Burke, Anne E.; Reeves, Matthew F.
Abstract : INTRODUCTION: Intrauterine devices (IUDs) are long-acting reversible contraceptive methods with comparable effectiveness to female sterilization, yet are cheaper and simpler to initiate. We sought to compare the characteristics of current IUD use and female sterilization among reproductive-aged women and to examine predictors of current IUD use. METHODS: We performed an analysis of female respondents from the 2006–2010 National Survey of Family Growth aged 15–44 years currently using IUDs or sterilization. Predictors of current IUD use were assessed using χ 2 analysis and logistic regression models. RESULTS: We identified 460 women currently using IUDs and 1, 804 women using sterilization. Of IUD users, 35.7% were older than 35 years, median parity was two, and 66.1% were married. Of women using sterilization, 68.3% were older than 35 years, median parity was three, and 68.3% were married. Women 15–24 years old were much more likely to use IUDs than sterilization compared with women age 40–44 years old (odds ratio [OR] 56.2, 95% confidence interval [CI] 24.8–127.2). Women with one child were more likely to use IUDs than sterilization compared with women with at least three children (OR 10.9, 95% CI 6.3–18.9). Women uncertain of future fertility were more likely than women who completed childbearing to use IUDs compared with sterilization (OR 7.1, 95% CI 2.3–22.0). CONCLUSION: Intrauterine devices are popular contraceptive methods for younger women, those with fewer children, and those unsure about future fertility. Despite equal contraceptive efficacy, easier initiation, and lower cost, IUDs are less commonly used by older women and women with more than three children.